A Proposed Model for The Future Foresight Skills of the Educational Planner in the Kingdom of Saudi Arabia - Alghurayr, Mashael Mohammed; Aljerasy, May Ibrahim; Albrahim, Taghreed Mohammad; Alburaidi, Sara Mohammed; Alkatheeri, Manar Mohammed (Journal of Educational and Psychological Sciences, 2022)
This study aimed to enhance the future foresight skills of the educational planner, by identifying the future foresight skills that are required to be available in the educational planner, from the point of view of strategic planning experts and future foresight experts and the mechanism of its measurement, and then presenting a proposed model to measure the future foresight skills of the educational planner. To achieve the objectives of the study, the quantitative approach was used using the Delphi method in two rounds and the resolution as a tool for this study, on a group of twenty (20) experts in the first round, and (15) fifteen experts in the second round. The results of the study concluded to present a proposed model for future foresight skills for the educational plan consisting of four main skills: personal skills (14 sub-skills), academic field (15 sub-skills), work skills (16 sub-skills), and technical field (8 sub-skills). The study presented a number of recommendations in the light of which, the most prominent of which are the implementation of initiatives and programs aimed at developing the level of educational planning, which contributes to enhancing the skills of future foresight among educational planners and designing training programs for educational leaders in general and educational planners in particular based on the proposed future foresight skills. .